Labor-Management Relations and Varieties of Capitalism - Martin R. Schneider (Global Labor Organization (GLO), 2021)
The varieties-of-capitalism (VoC) approach distinguishes liberal market economies (LMEs) such as the USA and coordinated market economies (CMEs) such as Germany based on institutional differences in terms of corporate governance, industrial relations, company relations as well as education and training. According to the VoC approach, firms differ in the ways in which they combine market and non-market mechanisms to coordinate their activities. Firms in LMEs are considered to rely more on market or exit mechanisms than firms in CMEs, which more often complement market with non-market or voice mechanisms. This chapter summarizes what has been learned from the VoC approach on the linkages between the institutional environment and labor-management relations. Various important lessons can be drawn. Employment protection legislation is a productive element within the institutional setup of CMEs. LMEs tend to induce strong overall wage dispersion, whereas in some CMEs such as Germany the labor market performance varies markedly by skill type and gender. The recent literature also indicates that the institutional setup is more complex than the VoC approach suggests, calling for revisions to the approach. In particular, some countries are hybrid economies that combine elements of both types of capitalism. The CME-LME dichotomy does not appreciate the true variety of country-specific skill systems. Finally, multinational enterprises overcome institutional boundaries of different types of capitalism in ways that were not included in the original VoC approach.
Keywords: J50; M12; P17; 330; varieties of capitalism; employment relationship; skill systems; employment protection